Diretrizes com base em avaliação do ciclo de vida para redução de emissões de dióxido de carbono em revestimentos de argamassa - Gama Junior, Antônio Claret de Almeida (2013)
Sustainable development is a highly discussed reality in world’s context. Related to that, it can be said that it is about respect with nature during economy and society development of a certain region. If so, with the growth of civil construction and industrialization of today’s world, each time growth atmospheric emissions, solids and liquids, harm the environment and causing damage to the greenhouse effect caused mainly by increasing the concentration of carbon dioxide in the atmosphere. Thinking about the impact caused by those emissions was created the tool of Life Cycle Assessment, which is capable to measure all emissions involved in services and materials life cycle. Using this tool in civil construction, specifically in the service of internal mortars, this paper aimed in making a comparison between two materials emissions of CO2, which are alternatives able to make the internal mortar, the regular mortar prepared in site and industrialized mortar. Going through the process of obtaining data along industry and sellers, and making a data collect about mortar consumption inside two constructions in the city of Goiânia, was possible do set the comparison, getting the conclusion that despite being highly industrialized, the industrialized mortar shows a better performance with regard to CO2 emissions, ie, emits a lower amount of gas to achieve the same service. Part of the explanation for that is the logistic adopted for using industrialized mortar, which requests a change in the using process. It is also possible to realize that the better performance toward regular mortar is due the high consumption of electricity needed to use this, making the Brazilian energy matrix responsible for a large amount of carbon dioxide emissions in the atmosphere.